Low temperature powder bed fusion of polyamide 6: transient process characteristics and process-dependent part properties - Schlicht, Samuel; Gabriel, Claus; Drummer, Dietmar (Progress in Additive Manufacturing, 2024)
The powder-based additive manufacturing of high-melting polyamides is impeded by unfavorable fracture properties and oxidation tendencies, limiting the technical applicability and the reuse of unfused powder. Overcoming these limitations through new processing strategies provides the opportunity for significantly extending the range of materials applicable for powder bed fusion processes. Based on fractal, locally quasi-simultaneous exposure strategies, a mesoscale compensation of thermal and crystallization-induced shrinkage is obtained, enabling the non-isothermal processing and stable layer formation of polyamide 6 at powder bed temperatures of 25 °C, 50 °C, and 75 °C. Thermographic in situ investigations reveal the layerwise quenching of discrete layers, leading to cooling rates exceeding − 250 K s−1 at 130 °C. Based on microscopic, mechanical, thermal, and spectroscopic investigations, insights into the structure formation and corresponding mechanical properties can be obtained, yielding reduced fractions of α-PA6 while increasing the elongation at break. The inherent layerwise quenching promotes the formation of microspherulitic morphologies while minimizing oxidation-induced material degradation, reflected in infrared spectroscopic material characteristics. Relying on obtained findings, process optimization strategies can be derived that enable the processability of high-melting polyamides at reduced temperatures, reducing the energy consumption of the build process while adapting underlying material characteristics based on accelerated intermediate cooling conditions. <